UJI AKTIVITAS TABIR SURYA FORMULA SEDIAAN LOSIO EKSTRAK METANOL DAUN MANGKOKAN (Nothophanax scutellarium Merr.) - Suryani Suryani; Rini Hamsidi; Nurlena Ikawati; Ahmad Zaeni; Hasnawati Hasnawati (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2014)
Leaves of mangkokan  (Nothophanax scutellarium Merr.) contain a potent antioxidant and sunscreen compounds. This plant potential to be developed into cosmetic products. One of cosmetic product that can be developed  using  natural  product  is  lotion.  This  research  aims  to  formulate  lotion  from  methanol  extracts  of leaves  mangkokan  and  determining  the  sunscreen  activity  of  lotion  with  various  concentration  of  the  extract 1%; 2.5%; 5%; 7.5%; and 10% using laboratory experimental design.  Preparation of mangkokan leaf extracts using methanol solvent by maceration method. Further tests conducted to determine the activity of sunscreen. Methanol extract of the leaves mangkokan then formulated to be lotion. Sunscreen activity of lotion was tested by  determaining  SPF  values.  Lotion  methanol  extract  of  leaves  mangkokan  resulting  the  highest  SPF  value contained in the methanol extract of the leaves mangkokan concentration of 10%. Keywords: mangkokan leaves, lotion, extract, lotion, sunscreen